William Zeckendorf, Place Ville-Marie, and the Making of Modern Montreal - Nerbas, Don (Urban History Review / Revue d'histoire urbaine, 2015)
The Place Ville-Marie development was central to the renovation of Montreal during the 1950s and 1960s. Its cruciform office tower transformed the city’s skyline and marked the removal of the city’s financial district from St. James Street to the new alley of skyscrapers on Dorchester Boulevard (now Boulevard René Lévesque). Earlier studies have emphasized the role of modern planning in the making of Place Ville-Marie and other post–Second World War urban redevelopment projects. This article advances an interpretation of Place Ville-Marie as a capital investment in the “production of space.” The project was a highly speculative effort by its developer, William Zeckendorf, to utilize monumental architecture to sell prestige to corporate tenants. This took place in specific, historically contingent, and politically contested circumstances. In a period when modernization was a powerful and popular idea, Zeckendorf cultivated a myth about Place Ville-Marie that accommodated and absorbed nationalist aspirations within Montreal and Canada that were fixed upon the panacea of modernization. While Zeckendorf’s financial woes and the overcapacity of office space that Place Ville-Marie helped create contradicted the project’s mythic image, Place Ville-Marie also embodied new capitalist values and the rise of new capitalist forces in the city.